2018
DOI: 10.1136/bmjopen-2017-018533
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the HIV undiagnosed population in Catalonia, Spain: descriptive and comparative data analysis to identify differences in MSM stratified by migrant and Spanish-born population

Abstract: ObjectiveUndiagnosed HIV continues to be a hindrance to efforts aimed at reducing incidence of HIV. The objective of this study was to provide an estimate of the HIV undiagnosed population in Catalonia and compare the HIV care cascade with this step included between high-risk populations.MethodsTo estimate HIV incidence, time between infection and diagnosis and the undiagnosed population stratified by CD4 count, we used the ECDC HIV Modelling Tool V.1.2.2. This model uses data on new HIV and AIDS diagnoses fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…In the period 1995–2018, 57.2% of tests were performed on MSM, 7.6% on SW (FSW plus MSW), 2.6% on PWID, 1.5% on transgender people and 45.2% on foreign nationals (including migrant population). A recent study showed that in Catalonia, 12.3% of those living with HIV were still undiagnosed, and this proportion was higher in migrants [ 28 ]. Therefore, in Catalonia, providing access to HIV POCT in the community is important, especially for populations facing barriers to accessing the healthcare system, such as the migrant population.…”
Section: Discussionmentioning
confidence: 99%
“…In the period 1995–2018, 57.2% of tests were performed on MSM, 7.6% on SW (FSW plus MSW), 2.6% on PWID, 1.5% on transgender people and 45.2% on foreign nationals (including migrant population). A recent study showed that in Catalonia, 12.3% of those living with HIV were still undiagnosed, and this proportion was higher in migrants [ 28 ]. Therefore, in Catalonia, providing access to HIV POCT in the community is important, especially for populations facing barriers to accessing the healthcare system, such as the migrant population.…”
Section: Discussionmentioning
confidence: 99%
“…Causes of HIV transmission among MSM have been well documented, such as sexual risk behaviors including unprotected sexual intercourses and multiple sex partners, as well as a high frequency of substance use and abuse [2,[5][6][7][8][9][10]. However, many MSM living with HIV do not acknowledge their HIV serostatus, ranging from 16% in the United States [11], 21% in New Zealand [12], 22% in Spain [13] to 86% in China [14] and 90.4% in Malawi [15]. Consequently, they receive delayed care, which threatens their health and accelerates HIV progression [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Lots of experts has been devoting to the estimation of HIV new infections and HIV undiagnoses in recent years [18][19][20], but accurate estimation of real-time HIV infection in China becomes challenging because of the differences in various transmission routes, patterns of risk behaviours, the intensities of interventions for various regions, high loss ratio of follow-up and etc [1,21]. HIV epidemic in Guangxi, representing national wide pattern of HIV infection to some extent, has new features including quick increase of HIV infections caused by heterosexual transmission [2,[9][10][11][12]22], increasing of reported cases with age older than 50 [10] and regional itself characteristics, which will bring new challenges to the estimation.…”
Section: Introductionmentioning
confidence: 99%